Digital Healthcare : is a Trend or Necessity? - Kristina Dewi, I Gusti Ayu Agung; Mahyuni, Luh Putu (Jurnal Kesehatan Masyarakat, 2024)
In the era of digital advancement, the government is actively endorsing different digital health apps. This trend is particularly noticeable in Indonesia, where consumer-focused eHealth services have gained extensive approval. The acceptance of these services has risen significantly over time, propelling Indonesia to a global ranking of third place in using health apps. This research intends to determine whether the inclination towards digital healthcare is genuinely embraced as a necessity, or if it’s just a passing trend. The study involves conducting a nationwide quantitative investigation across Indonesia among 418 users of mobile health apps, based on the UTAUT 2 theory which was modified according to research needs by adding variable FOMO. Data collection through online surveys and uses structural equation modeling (SEM-PLS), to assess the connections between these factors. They reveal that digital healthcare is not only embraced but also perceived as a necessity. While necessity-driven motivation remains dominant, the study also uncovers hedonic factors playing a role. This combination of necessity and trend-related aspects underscores the potential market for digital healthcare. The outcomes of this research bring promising news for developers of digital healthcare solutions. It reveals that there is a genuine demand and need for digital healthcare services.